Penerapan Unsur Tanah Jarang pada Struktur Rangka Persenjataan Militer (Kasus Struktur Rangka F-35 Lightning II) - Setiawan, Rudi; Aritonang, Sovian; Andreas N, R Djoko; Juhana, Riyadi (Rekayasa Material, Manufaktur dan Energi, 2023)
The rare earth element (REE) is not a free metal element or an individual pure mineral, generally in the form of compounds. To obtain rare earth element is done by extraction that requires modern technology with expensive costs. The use of REE is very important for the development of industry and modern technology. Seeing the potential and rapidly developing technology, the Rare Earth Metal in developed countries is currently being used as a mixture of materials in the manufacture of weapons. This journal will discuss the use of rare earth element for the F-35 Lightning II fighter. REE used in F-35 is a mixture for composite Graphite/Epoxy and Graphite/Bismaleimide, as elements Rhenium, Samarium, and Tantalum. This compost is used on the fuselage structure as an example for the Fuselage Center. The results of these alloys can increase aircraft performance, which is resistant to high temperatures, resistant to high pressure, and cannot be detected by radar (stealth). But also before being applied it needs accurate analysis of the negative impacts if the composites are implemented